Synthesis and biological evaluation of dual functionalized glutathione sensitive poly(ester-urethane) multiblock polymeric nanoparticles for cancer targeted drug delivery. Issue 43 (17th September 2015) - Kumar, Arun; Lale, Shantanu V.; Naz, Farhat; Choudhary, Veena; Koul, Veena
Abstract : Dual targeted redox responsive doxorubicin loaded polymeric nanoparticles were prepared and evaluated for anticancer efficacy. Abstract : Glutathione sensitive polymeric nanoparticles composed of poly(ester-urethane) and (-PCL-PEG-PCL-urethane-ss-) random multiblock copolymers with multiple disulfide linkages were developed for targeted doxorubicin delivery in cancer. The multiblock copolymers were synthesized via ring opening polymerization (ROP) of ε-caprolactone by polyethylene glycol followed by isomerization polymerization with hexamethylene diisocyanate (HMDI) and 2-hydroxyethyl disulfide. The polyethylene glycol (PEG) content of ∼20% in the multiblock copolymers led to the formation of nanoparticles with size ∼80 nm. A high doxorubicin loading content of ∼26% was achieved in the polymeric nanoparticles. Disulfide linkages in the multiblock copolymers facilitate nanoparticle degradation by glutathione (GSH), resulting in intracellular drug release. Drug release studies confirmed the glutathione sensitive nature of polymeric nanosystems by achieving ∼80% drug release at pH 5.5 in the presence of 10 mM GSH concentration as compared to ∼19% at pH 7.4. In vitro studies in breast cancer cell lines (MCF-7 and BT474) showed a ∼20 fold increase in cellular uptake efficiency of dual targeted nanoparticles with a subsequent higher apoptosis as compared to non-targeted polymeric nanoparticles. In vivo studies in Ehrlich's ascites tumor (EAT) bearing Swiss albino mice showed a superior tumor regression of ∼89% as compared to free doxorubicin (∼42%) without any significant toxicity. These promising results show the potential of the above synthesized multiblock copolymeric nanosystem as a drug delivery nanocarrier in cancer therapeutics with an enhanced antitumor efficacy and a reduced toxicity.